Semiflexible particles in isotropic turbulence - Ali, A; Plan, E; Ray, S; Vincenzi, D (American Physical Society, 2016)
The Lagrangian dynamics of semiflexible particles in homogeneous and isotropic turbulent flows is studied by means of analytically solvable stochastic models and direct numerical simulations. The stationary statistics of the bending angle shows a strong dependence on the dimension of the flow. In two-dimensional turbulence, particles are found in either a fully extended or a fully folded configuration; in three dimensions, the predominant configuration is the fully extended one. Such a sensitivity of the bending statistics on the dimensionality of the flow is peculiar to fluctuating flows and is not observed in laminar stretching flows.